Application of Green Practice in Food & Beverage Depart-ment to Increase Guest Satisfaction in Renaissance Bali Uluwatu Resort & Spa - Ni Putu Pande Dian Satya Dewi; I Gusti Putu Sutarma; Linna Sagitarini; Ni Nyoman Triyuni; Ni Made Sudarmini (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This study aims to apply green practice in the Food & Beverage Department to increase guest satis-faction and determine the most influencing variable in the department to increase guest satisfaction at the hotel. Research methods: This research data collection method was carried out by observation, interviews, ques-tionnaires, and a literature study. The sampling technique in this study used Accidental Sampling with a total sample of 55 respondents and 3 informants. Collecting data using an online questionnaire distributed to re-spondents using a google form link. The results of the data from the questionnaire were processed by con-ducting validity tests, reliability tests, classical assumption tests, multiple correlation tests, multiple linear re-gression tests, coefficients of determination, t-tests, and F-tests with SPSS 25 software for windows. The data analysis technique used descriptive qualitative analysis to determine the application of green practice in the Food & Beverage Department to increase guest satisfaction and quantitative analysis with a multiple linear regression test. It is used to determine the most influential variables in the Food & Beverage Department to increase guest satisfaction. Findings: The results show that the application of green practices has been carried out optimally in the Food & Beverage Department such as not using plastic materials, using materials from local farmers, and separating organic and non-organic waste. Implication: The results of the multiple linear regression test show that the most influential variable is green food at 7.426 and the coefficient of determination analysis test shows that green food is 83.4% which has a very strong relationship.